2014
DOI: 10.1002/jsfa.6757
|View full text |Cite
|
Sign up to set email alerts
|

Post‐harvest control of gray mold in table grapes using volatile sulfur compounds from Allium sativum

Abstract: The antifungal activity that allicin and diallyl trisulfide, which are the volatile compounds emitted by a garlic extract, exerted on conidia germination of B. cinerea may be considered as an alternative for the control of gray mold in table grapes after harvest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
(34 reference statements)
0
10
0
3
Order By: Relevance
“…Both EHA and DADS, DATS and allicin have showed to become bioactive at vapor phase (Curtis et al, 2004;Gándara-Ledezma et al, 2015), a characteristic that makes it easier to use them in a gaseous form to control B. cinerea, a pathogen causing gray mold on grape clusters. Due to marketing norms, table grape berries should not come into contact with liquids after being harvested (Codex Stan 255, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Both EHA and DADS, DATS and allicin have showed to become bioactive at vapor phase (Curtis et al, 2004;Gándara-Ledezma et al, 2015), a characteristic that makes it easier to use them in a gaseous form to control B. cinerea, a pathogen causing gray mold on grape clusters. Due to marketing norms, table grape berries should not come into contact with liquids after being harvested (Codex Stan 255, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This is a relevant aspect of table grape marketing because, after being harvested, the berries must not be in contact with liquid substances (Codex Stan 255, 2007). In a previous research, it was found that a hydroalcoholic extract of garlic (EHA) inhibited B. cinerea in vitro spore germination in a magnitude similar to that of allicin and dialyltrisulfide compounds (Gándara-Ledezma et al, 2015).…”
Section: Botrytis Cinereamentioning
confidence: 96%
See 3 more Smart Citations